2010
DOI: 10.1159/000265542
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of the Brief Agitation Rating Scale in a Large Sample of Norwegian Nursing Home Patients

Abstract: Background: Agitation and aggression are prevalent in dementia and put heavy strains on caregivers. Validated assessment tools measuring these symptoms are required to evaluate patients before therapy and during the follow-up period. Given the daily routine in nursing homes, abbreviated instruments are preferable. The Brief Agitation Rating Scale (BARS) is a short form of the Cohen-Mansfield Agitation Inventory. Our aim was to examine the Norwegian version of the BARS by performing a factor analysis. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Agitation was measured according to the NPI agitation score at each follow-up point, which could take one of nine values (0, 1,2,3,4,6,8,9,12), with higher values indicating more severe levels of agitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agitation was measured according to the NPI agitation score at each follow-up point, which could take one of nine values (0, 1,2,3,4,6,8,9,12), with higher values indicating more severe levels of agitation.…”
Section: Methodsmentioning
confidence: 99%
“…l Level 2b: lower-quality RCTs and higher-quality non-randomised studies (scoring ≤ 11). l Level 2c: moderate-quality non-randomised studies (scoring [6][7][8][9]. l Level 4: these scored < 6.…”
Section: Follow-up Ratesmentioning
confidence: 99%
“…The BARS is a subscale of the Cohen-Mansfield Agitation Inventory (CMAI) [44]. The Norwegian version [45,46] consists of 9 items: hitting, pushing, grabbing, wandering, restlessness, repetitive sentences, repetitive mannerisms, complaining and making strange noises. The frequencies of these symptoms are rated from 1 (never) to 7 (several times per hour), resulting in a minimum score of 9 and a maximum score of 63.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is in contrast to others, who has found that aggressive behaviour could be treated as a separate dimension for nursing home residents. [52] This further underscores the point that some IADL variables have a strong cognitive element. Thus, the distinction between physical and cognitive variables may be more relevant than that between ADL, IADL and cognitive variables.…”
Section: Discussionmentioning
confidence: 91%